Influence of Pressure and Temperature on X-Ray Induced Photoreduction of Nanocrystalline CuO - Kuzmin, Alexei; Anspoks, Andris; Nataf, L.; Baudelet, F.; Irifune, T. (Sciendo, 2018)
X-ray absorption spectroscopy at the Cu K-edge is used to study X-ray induced photoreduction of copper oxide to metallic copper. Although no photoreduction has been observed in microcrystalline copper oxide, we have found that the photoreduction kinetics of nanocrystalline CuO depends on the crystallite size, temperature and pressure. The rate of photoreduction increases for smaller nanoparticles but decreases at low temperature and higher pressure.
The authors are grateful to Prof. Alain Polian for providing NDAC cell. Parts of the present research have been carried out at the ODE beamline at SOLEIL.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; copper oxide; high-pressure; nanocrystalline; radiolysis; X-ray absorption spectroscopy